Significance of Sonographic Tissue and Surface Characteristics of Carotid Plaques - Tegos, Thomas J.; Kalomiris, Konstantinos J.; Sabetai, Michael M.; Kalodiki, Evi; Nicolaides, Andrew N. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Our hypothesis was that symptomatic and asymptomatic carotid plaques are different. The aim of this study was to identify the sonographic tissue and surface characteristics of plaques and their degree of stenosis that corresponded to these two clinical presentations.METHODS: We studied 81 symptomatic and 111 asymptomatic plaques (150 patients) having 50% to 99% stenosis on duplex scanning. These plaques were imaged on duplex and captured in a computer. We evaluated the gray-scale median (GSM) to distinguish hypoechoic (low GSM) from hyperechoic (high GSM) plaques, and the bending energy (BE), to distinguish plaques with irregular (high BE) versus smooth (low BE) surfaces.RESULTS: The symptomatic group corresponded to hypoechoic (median GSM, 4) and severely stenosed (median stenosis, 85%) plaques, whereas the asymptomatic group corresponded to hyperechoic (median GSM, 35) and moderately stenosed (median stenosis, 70%) plaques (P < .05 for both variables). The BE failed to separate the two groups; the mean BEs were 1.63 and 1.68 for the symptomatic and asymptomatic groups, respectively (P = .38).CONCLUSION: Our results suggest that echogenic characteristics and the degree of stenosis are the strongest predictors of carotid plaque behavior. The sonographic surface characteristics failed to qualify as an index of plaque instability.